A qualitative evaluation of a mental health literacy intervention for parents delivered through community sport clubs. (March 2020) - Hurley, Diarmuid; Swann, Christian; Allen, Mark S.; Vella, Stewart A.
Abstract: Intervention studies have rarely targeted parent mental health literacy despite its importance for adolescent mental health. This qualitative study evaluated the experiences of parents ( n  = 352) who participated in the Ahead of the Game mental health literacy workshop delivered through community sport clubs. Moreover, the study aimed to investigate the relevance, retention and use of intervention content by parents, assess the acceptability and feasibility of delivering mental health education through community sport clubs, and identify strategies for increased engagement. In total, 17 parents (13 mothers, four fathers) participated in semi-structured interviews up to one month after the workshop. Reflexive thematic analysis revealed that parents perceived mental health education as important and valuable, and believed the community sport club was an appropriate setting to discuss adolescent mental health. Parents reported increased awareness and knowledge of mental health disorders and help-seeking options, and increased confidence and preparedness to communicate and assist someone experiencing a mental health issue. The workshop stimulated conversation about mental health between parents and their children, and between parents within and outside the sport club community. Parents used information and resources provided in the workshop to help those in their networks and reflected back on the workshop when noticing changes in their adolescent's behavior. Potential additions to the workshop (as suggested by parents) included increased discussion among parents as well as opportunities for further information sessions or tailored online material. Future research might look to engage more fathers, actively encourage parents to aid in the recruitment of others, and investigate long-term adolescent mental health outcomes. Highlights: Parents reported increased awareness and knowledge of mental health disorders and help-seeking options. Parents perceived increased confidence and preparedness to assist someone experiencing a mental health issue. The intervention stimulated conversation about mental health within sport club communities. Parents made use of intervention information and resources to help others. Community sport clubs were perceived as an acceptable setting to discuss mental health.